EMPLOYEE PERFORMANCE AND COMPETENCE - Ratnawati Ratnawati; Warkianto Widjaja; Akbar Said; Rahma Saiyed; Kadeni Kadeni (Universitas 45 Surabaya, 2023)
The purpose of this study is to investigate and explain the impact of competence, organizational commitment, and career development on employee performance at the Tamansari Branch of PT Bank Rakyat Indonesia Bandung. Employees of the customer service executor of PT Bank Rakyat Indonesia Bandung, Tamansari Branch, were the focus of this study. The saturation sampling technique was used, with a total sample of 40 respondents. Data was gathered through the distribution of questionnaires. Multiple linear regression analysis was employed as the analysis technique. Employee performance at PT Bank Rakyat Indonesia Bandung, Tamansari Branch was positively and significantly influenced by competence, organizational commitment, and career growth, according to the findings.